Analisis Semantik Dalam Puisi “Hujan Bulan Juni” Karya Sapardi Djoko Damono - Endang Aristianti Gultom; Wike Afsari Sinaga; Inge Irawati; Cindy Jelita Sari; Yuliana Sari (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Poetry is the recording and interpretation of important human experiences transformed into a memorable and interesting form. Poetry is one type of literary work that is of interest to various groups and age groups. Not only reading poetry, some people are also interested in creating poetry. Linguistically, poetry is mostly free, not bound by specific rules. The use of figurative language sometimes makes it difficult to understand the meaning of beautiful words in poetry. The poem June Rainfall by Sapardi Djoko Damono is the subject of this research. The problem raised by the author is only limited to the meaning of words in this poem. The purpose of this research is to describe the meaning contained in the poem June Rainfall through semantic analysis, which focuses on analyzing lexical meaning, grammatical meaning, referential meaning, and figurative meaning. Qualitative descriptive method is used as the research method. The techniques used in this research include documentation techniques, library techniques, and note-taking techniques. The results of the discussion show that this poem can be analyzed through semantic studies.